WHITEBOARDS INTERACTIVE IN THE EDUCATIONAL PROCESS - WARZOCHA, Tomasz (Trends in education, 2011)
This article presents possibilities of using modern information technologies in educational process. At the start of a brief description of the information technology and then discusses the use of interactive whiteboards in education. The article shows the advantage that interactive whiteboards have the ``regular'' tables, based on studies conducted among teachers and students.
Keywords: Interactive whiteboard; education; new technologies; the educational process.